2016
DOI: 10.1371/journal.pone.0147675
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Distribution of Fetal Microchimerism in Local Breast Cancer Environment

Abstract: Fetal cells enter maternal circulation during pregnancy and persist in the woman’s body for decades, achieving a form of physiological microchimerism. These cells were also evidenced in tumors. We investigated the frequency and concentration of fetal microchimerism in the local breast cancer environment. From 19 patients with confirmed breast neoplasia, after breast surgical resection, we collected three fresh specimens from the tumor core, breast tissue at tumor periphery, and adjacent normal breast tissue. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
11
0
3
Order By: Relevance
“…Given results of previous studies showing increased fetal microchimerism in tumors compared to surrounding normal tissue (10, 32, 35), we wondered whether microchimerism might be similarly increased in brain tumors compared to normal brain. We identified slides that contained brain parenchyma without signs of tumor involvement and used these to assess whether microchimerism prevalence differs in surrounding, apparently normal, tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given results of previous studies showing increased fetal microchimerism in tumors compared to surrounding normal tissue (10, 32, 35), we wondered whether microchimerism might be similarly increased in brain tumors compared to normal brain. We identified slides that contained brain parenchyma without signs of tumor involvement and used these to assess whether microchimerism prevalence differs in surrounding, apparently normal, tissues.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of microchimeric cells in blood has been prospectively associated with decreased risk for breast cancer and increased risk for colon cancer (22). In addition, microchimeric cells have been identified in tumors of the breast, lung, thyroid, cervix and skin (7, 10, 13, 32, 33, 35). In these studies, the frequency of microchimeric cells was increased in malignant neoplasms compared to surrounding normal tissue (10, 32, 35) and benign neoplasms (13, 33).…”
Section: Introductionmentioning
confidence: 99%
“…However, they did not identify the familial variant in the tumor tissue of any of the phenocopies. Ultimately, their study did not support their hypothesis (Mitchell et al, 2018).…”
Section: Discussionmentioning
confidence: 79%
“…Their role in carcinogenesis remains unknown. Some studies suggest their protective role in breast [ 64 , 67 ] and other maternal cancers, while others point towards their unfavorable role in promoting tumorigenesis [ 66 ]. However, so far no studies showed that fetal cells can directly give rise to cancer by forming a malignant clone in a mother, although some research suggests that it is possible [ 68 ].…”
Section: Discussionmentioning
confidence: 99%